Tourism From Empirical Research Towards Practical Application - Butowski, Leszek (IntechOpen, 2016)
Tourism is that area of activity of contemporary man that touches on various fields of human interest. Representatives of numerous academic disciplines find it intriguing for its exceptionally interdisciplinary character. Conditions for and consequences of the development of tourism are investigated, among others, by economists, geographers, sociologists, experts in culture, anthropologists, management and social policy specialists and even by representatives of some natural sciences. Researchers dealing with tourism need to meet strict methodological requirements, but they get access to a very interesting subject of scientific inquiry, which combines social, cultural, economic and environmental aspects to create an ontologically new quality offering epistemological challenges.